Mercado mayorista como mecanismo de abaratarlos costos en la intermediación de los productos agrícolas de consumo, caso de estudio; cantón Quevedo, provincia de Los Ríos - Cedeño Mendoza, Kerlly Yuliana (2015)
This thesis was developed in Quevedo City of the province of Los Rios, for which information was obtained in the Public Enterprise of Municipal Markets concerning wholesalers and retailers of the QuevedoCity and lasted 180 days time which surveys, interviews and other processes to establish that the presence of a wholesale market to be created intended to be regarded as a place that can offer better prices to consumers and is expected to be a meeting point for producers, distributors apply and buyers, eliminating the surcharges that many brokers have justified by overspending in the preservation of agricultural products which leads to more expensive products.This research provides investors and interested the most accurate in order to support decision-making in any line information regarding the Wholesale Market Project of the city of Quevedo as a local development plan well for Quevedeña.Research is through the introduction where the research model with its overall objective is specified: To analyze the socioeconomic impact with the implementation of a wholesale market as a means of reducing the intermediation costs in agricultural consumer products, case study; Quevedo City, Los Rios province, and as specific: a.) Perform a diagnosis of the current situation in the markets intermediation Quevedo City, b) Consider the impact of a wholesale market in the intermediation process fruits.and vegetables., c) Develop a proposal for the implementation of a wholesale market that allows the organization and distribution of fruits and vegetables, merchants of Quevedo City, as an alternative solution. It is presented in Chapter I, the contextual framework: where all of the conceptual foundations are located; in Chapter II, the theoretical framework: is where the concepts of key words and phrases of Research; in Chapter III, the research methodology: the reader will find the methods and materials used in the research; Chapter IV Results and Discussion are located: obtained based on surveys and interviews with wholesalers, retailers and users; in Chapter V, the proposal is presented, that indicates the creation of a wholesale market as a means of reducing the intermediation costs of agricultural products consumption in the Quevedo City; in Chapter VI, the conclusions and recommendations made in the development of research are described; in Chapter VII, the bibliography, where all authors consulted various texts will be presented; Finally Chapter VIII, which are the Annexes, is where the evidence of Research will be located.